Vitisma coriacea sp.n. (Insecta: Dictyoptera) from the mid-Cretaceous in northern Myanmar, first record of the genus in amber - Sendi, Hemen (Zootaxa, 2024)
The genus Vitisma Vršanský, 1999 is characterised by a shield-like, convex pronotum with transverse margins, scleroritized forewings with sometimes white macula, long clavus and rather simplified venation (simple Sc, straight and expanded M veins, CuA narrow and branched, A simple, R reaching apex). The hindwing venation is similar to the Blattulidae with a distinct pterostigma, but R1 is comb-like and CuA branched. The first record of Vitisma coriacea sp. n. in Burmese amber extends its palaeogeographic distribution to Gondwana, similar to other Umenocoleoidea. So far, the genus was only known from sediments in Spain, Russia, Mongolia, and possibly Japan. It also suggests that representatives of Vitisma inhabited warmer, tropical forest biomes.